Hoàn nguyên than hoạt tính bằng phương pháp oxy hóa xúc tác dị thể lỏng - rắn - Hùng, Trần Văn; Thoa, Trần Thị Kim; Thu, Nguyễn Thị; Phú, Nguyễn Hữu (VNU Journal of Science: Natural Sciences and Technology, 2009)
Abstract